Intuitions of future in “existential diaries” of 1920–1930s: Grigory Tseretely, Mikhail Prishvin, Gustav Shpet - T. . Schedrina (Высшее образование в России, 2022)
A key theme of this article is the relation of the eminent Russian intellectuals: scientist (Grigory Tseretely), writer (Mikhail Prishvin), philosopher (Gustav Shpet) to educational reforms of 1920–1930s in Soviet Russia expressed in their letters and diary notes. The author considersthese records to be an invaluable existential experience which bears evidence of historical dependency of the modern state of intellectual culture and education system in Russia.